2022
DOI: 10.3390/md20100626
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides from Skipjack Tuna Cardiac Arterial Bulbs: Preparation, Identification, Antioxidant Activity, and Stability against Thermal, pH, and Simulated Gastrointestinal Digestion Treatments

Abstract: Cardiac arterial bulbs of Skipjack tuna (Katsuwonus pelamis) are rich in elastin, and its hydrolysates are high quality raw materials for daily cosmetics. In order to effectively utilizing Skipjack tuna processing byproducts-cardiac arterial bulbs and to prepare peptides with high antioxidant activity, pepsin was selected from six proteases for hydrolyzing proteins, and the best hydrolysis conditions of pepsin were optimized. Using ultrafiltration and chromatographic methods, eleven antioxidant peptides were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…The cell viability of TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) groups were 70.15 ± 3.98%, 66.17 ± 5.04% and 65.20 ± 1.66%, respectively, which was significantly higher than those of the model group and other eight peptide groups ( p < 0.001), suggesting that they could significantly alleviate the oxidative stress damage of HaCaT cells caused by UVB radiation. This finding was in agreement with the previous results that TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) exhibited higher antioxidant ability among 11 antioxidant peptides (TCP1-TCP11) [ 30 ]. Therefore, the protective function and mechanism of TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) on the UVB-irradiated HaCaT cell model will be further discussed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The cell viability of TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) groups were 70.15 ± 3.98%, 66.17 ± 5.04% and 65.20 ± 1.66%, respectively, which was significantly higher than those of the model group and other eight peptide groups ( p < 0.001), suggesting that they could significantly alleviate the oxidative stress damage of HaCaT cells caused by UVB radiation. This finding was in agreement with the previous results that TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) exhibited higher antioxidant ability among 11 antioxidant peptides (TCP1-TCP11) [ 30 ]. Therefore, the protective function and mechanism of TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) on the UVB-irradiated HaCaT cell model will be further discussed.…”
Section: Resultssupporting
confidence: 93%
“…Elastin hydrolysate of tuna cardiac arterial bulbs was usually used in daily cosmetics. Then, eleven antioxidant peptides, including QGD (TCP1), GEQSN (TCP2), PKK (TCP3), GPQ (TCP4), GEEGD (TCP5), YEGGD (TCP6), GEGER (TCP7), GEGQR (TCP8), GPGLM (TCP9), GLN (TCP10), and GDRGD (TCP11), were purified and identified from its hydrolysate in our previous research, and TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) were found to have significantly radical scavenging ability and protective function on H 2 O 2 -damaged DNA and HepG2 cells [ 30 ]. Therefore, the objectives of the study were to systematic research the cytoprotective function of TCP3 (PKK), TCP6 (YEGGD) and TCP9 (GPGLM) on UVB-irradiated HaCaT Cells through antioxidant and anti-apoptotic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, its amino acid sequence and composition with a richness of hydrophobic amino acid could contribute to such high bioactivities. This was reported by several authors in different studies [ 30 , 36 ]. Therefore, the F-A was subjected to a further analysis with LC-MS/MS to identify the sequence of the active peptides.…”
Section: Resultssupporting
confidence: 77%
“…Numerous studies have found that a few key factors, such as molecular weight, amino acid compositions, and amino acid sequence, play critical roles in bioactivity [ 30 , 36 ]. Conventionally, in order to obtain a high purity of bioactive peptides, ion exchange chromatography and reverse-phase HPLC have been used to purify bioactive peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Alcalase hydrolysate of Antarctic Krill had the highest radical scavenging ability among the five hydrolysates [ 56 ]. Nangnoi strain hydrolysate generated by alcalase showed the highest activities among the three hydrolysates [ 57 ]. In the study, MSBH produced by papain shows the highest activity further proving this conclusion that specificity and conditions of proteases are the key factors for the generation of APs.…”
Section: Discussionmentioning
confidence: 99%